Reproductive Performance of Dairy Cows in Relation to Genotype, Age, Parity, Body Weight and Body Condition Score at Rajshahi District of Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
The present study was carried out from selected areas at Rajshahi district to evaluate the reproductive performance of dairy cows in relation to breed/genotype, age, parity, body weight and body condition. A total of 500 cows selected and data were collected directly from the dairy farms owner by using pre-tested questionnaires during the period from September 2013 to December 2014. The average reproductive performance (RP) were recorded as age at puberty (AP) 26.42±0.22 m, age at first calving (AFC) 35.48±0.22 m, post-partum heat period (PPHP) 121.85±3.48 days, service per conception (S/C) 1.93±0.04, days open (DO) 136.80±3.57 days and calving interval (CI) 401.04±3.94 days. Genotype had significant effect (P